2017
DOI: 10.3233/jad-161162
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Functional Decline in Prodromal Alzheimer’s Disease

Abstract: BACKGROUND:Little is known of possible associations between Alzheimer's disease (AD) biomarkers and instrumental activities of daily living (IADL) change over time. OBJECTIVE:The present study seeks to identify relationships between baseline imaging and fluid biomarker profiles, and decline in IADL utilising data collated from the AD Neuroimaging Initiative (ADNI) cohort. METHODS:Generalised estimating equations analysis, adjusted for cognitive deterioration, was applied to a cohort of 509 individuals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…First, these findings are consistent with the current literature on AD diagnostic strategies, that shows higher accuracy for FDG-PET as compared to other biomarkers ( Bloudek et al, 2011 ; Dukart et al, 2015 ; Fellgiebel et al, 2007 ; Iaccarino et al, 2017 ; Landau et al, 2010 ; Perani et al, 2016 ; Robb et al, 2017 ; Shaffer et al, 2013 ; Yuan et al, 2009 ). Of note, a recent study on the prognostic value of the NIA-AA ( McKhann et al, 2011b ), IWG-2 and IWG-1 criteria ( Dubois et al, 2007 , Dubois et al, 2014 ), showed that classification based on the NIA-AA criteria for AD dementia diagnosis, in which amyloid PET and FDG-PET biomarkers are considered, reached the highest prediction accuracy in a clinical setting ( Vos et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, these findings are consistent with the current literature on AD diagnostic strategies, that shows higher accuracy for FDG-PET as compared to other biomarkers ( Bloudek et al, 2011 ; Dukart et al, 2015 ; Fellgiebel et al, 2007 ; Iaccarino et al, 2017 ; Landau et al, 2010 ; Perani et al, 2016 ; Robb et al, 2017 ; Shaffer et al, 2013 ; Yuan et al, 2009 ). Of note, a recent study on the prognostic value of the NIA-AA ( McKhann et al, 2011b ), IWG-2 and IWG-1 criteria ( Dubois et al, 2007 , Dubois et al, 2014 ), showed that classification based on the NIA-AA criteria for AD dementia diagnosis, in which amyloid PET and FDG-PET biomarkers are considered, reached the highest prediction accuracy in a clinical setting ( Vos et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…To overcome this limit, diagnostic biomarkers such as neuroimaging (i.e., MRI, FDG-PET and amyloid-PET) and cerebrospinal fluid-CSF (i.e., Aβ42, total (t-Tau) and phosphorylated (p-Tau) Tau measures) have been included in the current research criteria for “MCI due to AD” ( Albert et al, 2011 ). Among these biomarkers, the FDG-PET patterns of hypometabolism seem to be particularly accurate in predicting conversion from MCI to dementia, when compared to other biomarkers ( Anchisi et al, 2005 ; Bloudek et al, 2011 ; Dukart et al, 2015 ; Fellgiebel et al, 2007 ; Landau et al, 2010 ; Perani et al, 2016 ; Prestia et al, 2013a ; Robb et al, 2017 ; Shaffer et al, 2013 ; Yuan et al, 2009 ). Notably, a recent meta-analysis on a large sample of MCI (N = 97) has shown that adding FDG-PET imaging information to clinical data provides a better prediction of conversion from MCI to dementia in comparison with clinical data alone, with misclassification rate dropping from 41.3% (clinical data alone) to 27.2% (combined clinical and FDG-PET data) ( Shaffer et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant difference in [ 18 F]FDG SUVR in temporal gyrus between the two groups. It has been reported that medial temporal regions were also often affected in AD [47] . The decreased [ 18 F]FDG uptake in both the angular and posterior cingulate regions, not in the temporal area, in the group with ventriculomegaly made this biomarker profile look unlike typical AD.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis of MiND and MaND due to AD was based on the DSM-5 diagnostic criteria [20] and on the diagnostic guidelines of the National Institute on Aging-Alzheimer Association [5,6]. In individuals without cognitive impairment, neither cognitive deficits nor functional impairment were detected [21,22]. The clinician who established the diagnoses was blind to the individual performance on COGTEL, COGTEL+ and 3MS.…”
Section: Participantsmentioning
confidence: 99%